Benefits of using cannabidiol in the treatment of motor and non-motor symptoms of Parkinson's disease: A systematic review (Research, Society and Development, 2025)
Parkinson's Disease (PD) is a chronic neurodegenerative condition, common in people over 65 years of age, characterized by the loss of dopaminergic neurons in the substantia nigra, which results in a decrease in dopamine in the brain. Conventional treatments, such as dopamine administration, have limited effectiveness over time, which can cause tardive dyskinesia. Seeking new therapeutic options, cannabinoids, such as cannabidiol (CBD), have been investigated due to their potential to modulate several biological pathways, including the reduction of motor and non-motor symptoms, in addition to combating inflammation and oxidative stress. This study aimed to carry out a Systematic Literature Review, which evaluated the effects of CBD on the motor and non-motor symptoms of PD, following the PRISMA protocol. Articles were searched in English, Portuguese and Spanish in the PubMed and Lilacs databases until 2023. The studies revealed varied results: some indicated benefits in pain control and quality of life, but also pointed out adverse effects such as drowsiness and dizziness. The effectiveness of CBD in improving motor symptoms has been inconsistent, and the combination with THC has had a negative impact on cognition in some patients. Studies suggest that CBD may be useful in treating the non-motor symptoms of PD, but more rigorous research with larger samples is needed to confirm its long-term impact and determine which patients would benefit most from this therapy.